Variability of environmental factors of an eastern Mediterranean Sea river influenced coastal system - K.AR. KORMAS; A. NICOLAIDOU; M. THESSALOU-LEGAKI (Mediterranean Marine Science, 2003)
Spercheios River discharge rates of nutrients, suspended particulate matter (SPM) and particulate organic carbon (POC) and seawater concentrations of these parameters as well as chlorophyll a(chl a) were measured in the Maliakos Gulf, Greece, on a monthly basis between 1992-1993. From all the nutrients measured, silicate showed the highest discharge rates followed by nitrate, phosphate and nitrite. The river introduced significant amounts of SPM (8.5 – 35.5 Kg d -1 ) with very low POC content (